Contabilidades societária e gerencial: diferenças e fatores críticos na integração - Ferreira, Leticia Longarini (2012)
In the exercise of our accounting activities we find two branches of accounting - corporate and management accounting,, which differ in many aspects studied by several authors of the field. Both accounting branches mentioned, each one with its purpose - customer focus and needs to be met, have a history of similarities and differences. Some of these differences become critical factors that may prevent them to be integrated. This takes many companies to have two separated records and accompaniments for the preparation and presentation of numbers, which eventually also present a distinct lack of reliability and fidelity of the numbers and the bases of preparation and control. This research aims to present the concepts of these two accounting branches - corporate (also called a financial accounting) and management, presenting the main aspects that rule both. It also aims to list the differences between them, pointing out possible approaches, highlighting the critical factors in the integration, including the information system to make it possible to minimize the risks posed by such critical factors through a proposed integrative model. This model includes the preparation of a Balance Sheet and Income Statement for the year, called "General", which aim to serve the public, both corporate and management accounting (external and internal users), without losing the integrity and quality of information